Factors Influencing Patient Satisfaction on Service Quality at Gynecology Polyclinic at Harapan Insan Sendawar General Hospital - Sitti Fatimah; Jasmawati; Rivan Firdaus (Formosa Journal of Science and Technology, 2022)
This research was conducted to determine the factors that influence patient satisfaction. The type of research used is quantitative research with a cross sectional approach. This research was conducted at the gynecology polyclinic at Harapan Insan Sendawar General Hospital from June to July 2022. The population in this study was 592 people, then samples were taken using purposive sampling, 65 respondents who visited the gynecology polyclinic. The data analysis technique used was univariate analysis and bivariate analysis using somers'd test. After analyzing the data, the results obtained were a p-value of 0.000 (p > 0.05) so that it could be concluded that there was an influence on responsiveness, assurance, reliability, empathy, and tangible factors on patient satisfaction in obstetrical polyclinics.